Effect of khat chewing on periodontal pathogens in subgingival biofilm from chronic periodontitis patients - Al-Hebshi, Nezar Noor; Al-Sharabi, Ali Kaid; Shuga-Aldin, Hussein Mohammed; Al-Haroni, Mohammed; Ghandour, Ibrahim (Elsevier, 2010)
Data on the oral health status and treatment needs among Yemeni children are lacking. Objectives: To assess caries prevalence, treatment needs and gingival health status among school children in Sanaa City and to examine how these are affected by age, gender and khat chewing. Methods: 1489 children (6- to 14-year old) were randomly selected from 27 schools representing all nine districts of Sanaa City. Dental caries and treatment needs were evaluated using standard WHO oral survey methods. The plaque index (PI), calculus index (CI) and the gingival index (GI), recorded at the six Ramfjords teeth, were used to assess gingival health status. Results: 4.1% of the study subjects were caries-free. Prevalence of these was significantly higher among the males. Overall, mean dmfs, dmft, DMFS and DMFT scores were 8.45, 4.16, 3.59 and 2.25 respectively. The decayed component accounted for >85% of the scores. The highest dmfs/dmft means were found among the 6-8?years age group, while the highest DMFS/DMFT means were scored by the 12-14?years age group. The need for restorative treatment and extractions was high; the former was significantly higher among the females. All subjects had gingivitis; the mean PI, CI and GI were 1.25, 0.3 and 1.36 respectively. Khat chewing did not affect caries experience; however, it was significantly associated with higher PI, CI and GI scores. Conclusions: The prevalence of caries, gingivitis and treatment needs among children in Sanaa city is high. More surveys in other Yemeni cities to generate comprehensive data are required.